تأثير تقلبات قرينة النينو على تقلبات الأمطار السنوية في الأردن - عنانبة، صباح ابراهيم (جامعة النجاح الوطنية, 2017)
تحلل هذه الدراسة تأثير تقلبات النينو على تقلبات الأمطار في الأردن خلال الفترة من عام-1960 2014 م. وقد استخدم في عملية التحليل عدد من الأساليب الإحصائية المناسبة مثل المتوسطات المتحركة - الفروقات التراكمية والانحدار والارتباط. وذلك بتحليل بيانات الأمطار وقرينة النينو في عدد من المحطات المناخية الأردنية. وتبين نتائج الدراسة وجود علاقة طردية واضحة بين التقلبات في النينو وتقلبات مماثله للأمطار في الأردن في كل من مناطق الشمال والوسط، يوجد للعلاقة بين تقلبات النينو وتقلبات الأمطار دلالة إحصائية في منطقتي الشمال والوسط، بينما لم تبلغ تلك العلاقة مستوى الدلالة في منطقة الجنوب.
This study analyzes the Impact of the Nino Index Fluctuations on the Annual Rainfall in Jordan during the period 1960-2014. Several appropriate statistical techniques are used in the analysis of annual rainfall in a sample of rainfall stations, including: Moving Averages, Accumulated Sums, Linear Regression, Correlation. The main results of this study suggest significant relationship between periodicities in both; the Niño index and annual rainfall in Jordan, especially in the northern and central, regions where most of the annual rainfall is associated with Mediterranean depressions. The relationship is weak and insignificant in the south and east where instability conditions and khamasin depression contribute more to the total annual rainfall. Short periodicities of four years where found in annual rainfall associated with similar periodicities in el-nino.
Keywords: الأمطار السنوية -- قرينة النينو -- الفروقات التراكمية -- الأردن